Whole-Brain Adaptive 70-kVp Perfusion Imaging with Variable and Extended Sampling Improves Quality and Consistency While Reducing Dose - Corcuera-Solano, I.; McLellan, A.M.; Doshi, A.H.; Pawha, P.S.; Tanenbaum, L.N. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Despite common use of CTP to assess cerebral hemodynamics in the setting of ischemia, concerns over radiation exposure remain. Our aim was to evaluate the efficacy of an adaptive 70-kVp (peak) whole-brain CTP protocol with variable sampling intervals and extended duration against an established fixed-sampling, limited-period protocol at 80 kVp. MATERIALS AND METHODS: A retrospective analysis of 37 patients with stroke scanned with conventional (n = 17) and variant-protocol (n = 20) whole-brain CTP was performed. We compared radiation dose, parametric map quality, and consistency of full-contrast circulation capture between a modified 70-kVp protocol, with 20 whole-brain passes at variable sampling intervals over an extended sampling period, and a conventional 80-kVp CTP examination with 24 passes at fixed-sampling intervals and a more limited scanning window. Mann-Whitney U test analysis was used to compare both protocols. RESULTS: The 70-kVp CTP scan provided superior image quality at a 45% lower CT dose index volume and 13% lower dose-length product/effective dose compared with the conventional 80-kVp scan. With respect to the consistency of contrast-passage capture, 95% of the adaptive, extended protocol continued through the venous return to baseline, compared with only 47% by using the conventional limited-length protocol. Rapid sampling during the critical arterial arrival and washout period was accomplished in nearly 95% with both the variable and fixed-sampling-interval protocols. CONCLUSIONS: Seventy-kilovolt (peak) CTP with variable and extended sampling produces improved image quality at lower radiation doses with greater consistency of full contrast passage capture. CTDIvolCT dose index volumeDLPdose-length product